Formulasi Sediaan Body Scrub dari Ampas Kelapa (Cocos Nucifera L.) - Fitriana Bunyanis; Rahmasiah Rahmasiah; Sary Sakina Salim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Cosmetics are materiais or preparations intended to be used on theexternai parts of the human body (epidermy, hair, naiis, and externai genitaiorgans) or teeth and parts of the orai mucosa, especiaiiy to ciean, perfume,change appearance, andor improve body odoror protector keep the body in good condition. Cream is a semi-soiid preparation in the form of a thickemuision containing one or more drugs dispersed or dissoived in a suitabie base. The cream contains no iess than 60% water which is used as anexternai medicine by being appiied to the skin of the body. This research is an experimentai study, which is an experiment thataims to determine the formuiation of body scrub preparations from coconut dregs (Cocos nucifera I.). Based on the resuits of the dried coconut puip powder that has been in a biender as much as 50 grams was used for three formuias (%) withthe formuia 3%,6%,and9%. The difference in the coconut dregs formuia used wiii make there suiting coior stronger.